2013
DOI: 10.1103/physrevb.88.174517
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structures and interplay between rare-earth Ce and Fe magnetism in single-crystal CeFeAsO

Abstract: Neutron and synchrotron resonant x-ray magnetic scattering (RXMS) complemented by heat capacity and resistivity measurements reveal the evolution of the magnetic structures of Fe and Ce sublattices in a CeFeAsO single crystal. The RXMS of magnetic reflections at the Ce L-II edge shows a magnetic transition that is specific to the Ce antiferromagnetic long-range ordering at T-Ce approximate to 4 K with short-range Ce ordering above T-Ce, whereas neutron diffraction measurements of a few magnetic reflections ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
3
20
2
Order By: Relevance
“…This is different from the itinerant CeFeAsO with a much lower ordered Fe moment of ∼ 0.9µ B compared to the 4 µ B expected from a localized moment 8 . The inplane checker-board-like AFM structure of the C-type order in CeMnAsO in T < T N suggests that the NN interaction J 1 is dominant whereas inplane nextnearest-neighbor (NNN) interaction J 2 is very weak or negligible.…”
Section: D Magnetic Interactions and Absence Of T-o Structural Trcontrasting
confidence: 70%
See 1 more Smart Citation
“…This is different from the itinerant CeFeAsO with a much lower ordered Fe moment of ∼ 0.9µ B compared to the 4 µ B expected from a localized moment 8 . The inplane checker-board-like AFM structure of the C-type order in CeMnAsO in T < T N suggests that the NN interaction J 1 is dominant whereas inplane nextnearest-neighbor (NNN) interaction J 2 is very weak or negligible.…”
Section: D Magnetic Interactions and Absence Of T-o Structural Trcontrasting
confidence: 70%
“…1. Similar to the tetragonal structure in RFeAsO (R is rare earth element) 8 or LaMnAsO 14 , the structure of CeMnAsO consists of MnAs and CeO layers where the Mn…”
Section: Amentioning
confidence: 92%
“…We find no evidence of Fe moment reorientation at the onset of Ce 3+ moment ordering in Ce 2 O 2 Fe 2 OSe 2 (which we expect our analysis to be sensitive to, given the relatively large moments on Fe sites). This is in contrast to CeMnAsO [14] and CeFeAsO [13], where some reorientation of transition metal spins has been reported at T N,Ce . The lack of any spin reorientation in Ce 2 O 2 Fe 2 OSe 2 may reflect the Ising-like nature of the Fe ordering, with the local anisotropy of Fe directing moments oriented along Fe-O(2) bonds and parallel to the expected Ce easy axis.…”
Section: Discussioncontrasting
confidence: 57%
“…Although the superconductivity arises in the iron arsenide layers, the Ln 3+ cation has a significant role in both tuning the superconducting T c in the doped materials [1,4] and in defining the magnetism of the parent nonsuperconducting materials (such as the spin reorientations in NdFeAsO [5] and PrFeAsO [6]). This has led to much research into the interplay between transition metal and lanthanide magnetic sublattices in these and related mixed-anion systems [7][8][9][10][11][12][13][14][15][16][17][18][19] [23] and a collinear model [10,22]. Recent work suggests that the 2-k model is the more likely [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Fe 2+ moments of CeFeAsO order antiferromagnetically in the ab plane at T N,Fe = 140 K [25] while the Ce 3+ moments couple strongly with the Fe 2+ moments at relatively high temperatures [30], before developing a long range order below ∼3.7 K with moments predominantly in the ab plane [25]. Recent studies suggested some reorientation of the Fe moments within the ab plane at the onset of the long range order of the Ce moments [31]. The Ce 3+ ions influence the iron magnetic sublattice, and can also induce exotic properties such as Kondo screening of the local moment in closely-related CeFePO [32] and CeRuPO [33].…”
Section: Introductionmentioning
confidence: 99%